FORMATION OF HIGHLY SPECIALIZED CHATBOTS FOR ADVANCED SEARCH - Yarovyi, Andrii; Kudriavtsev, Dmytro (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2024)
In this research, the formation of highly specialized chatbots was presented. The influence of multi-threading subject areas search was noted. The use of related subject areas in chatbot text analysing was defined. The advantages of using multiple related subject areas are noted using the example of an intelligent chatbot.